A framework for programmatically designing user interfaces in JavaScript. Issue 3 (7th September 2015) - Larkin, Henry
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the feasibility of creating a declarative user interface language suitable for rapid prototyping of mobile and Web apps. Moreover, this paper presents a new framework for creating responsive user interfaces using JavaScript. Design/methodology/approach – Very little existing research has been done in JavaScript-specific declarative user interface (UI) languages for mobile Web apps. This paper introduces a new framework, along with several case studies that create modern responsive designs programmatically. Findings – The fully implemented prototype verifies the feasibility of a JavaScript-based declarative user interface library. This paper demonstrates that existing solutions are unwieldy and cumbersome to dynamically create and adjust nodes within a visual syntax of program code. Originality/value – This paper presents the Guix.js platform, a declarative UI library for rapid development of Web-based mobile interfaces in JavaScript.